Developing a PBL-Based Interactive Storybook to Improve Reading Comprehension of Grade III Elementary School Students - Rahma Halipah; Mahpudin; Budi Febriyanto; Yuyun Dwi Haryanti; Aji Septiaji (LPPM Universitas Pendidikan Mandalika, 2026)
This study aims to develop, test the feasibility, measure the practicality, and examine the effectiveness of a PBL-based interactive storybook entitled “Misteri Bola Kertas” in improving students’ reading comprehension skills as measured by Barrett’s Taxonomy. The study employed a Research and Development (R&D) approach using the 4D model (Define, Design, Develop, Disseminate) and a mixed-methods design. Data were collected from 26 third-grade students using reading comprehension tests, expert validation questionnaires, and user response questionnaires, and were analyzed using descriptive statistics, N-gain scores, and paired-sample t-tests. The results reveal a significant improvement in students’ mean scores from 67.81 to 83.65 (N-gain = 0.56, moderate category; p < 0.001). This improvement was supported by expert validation of 81.53% (feasible), student responses of 93.75%, and teacher responses of 88.5% (both categorized as very practical). Although the learning media addresses all five levels of Barrett’s Taxonomy, it places particular emphasis on higher-order comprehension skills, specifically reorganization, inferential, and evaluative comprehension, which were identified as the most critical areas of student difficulty. These higher-order thinking processes are facilitated through interactive physical features, including pull-tab mechanisms that support information sequencing, flip-the-flap prompts that encourage synthesis of implicit narrative cues, and Velcro-based activities that engage students in kinesthetic evaluation of moral decisions, each operationalizing a distinct level of Barrett’s Taxonomy. These findings contribute to the literature by demonstrating that the structural integration of PBL phases into physical interactive print media constitutes an effective pedagogical approach. The study also offers practical implications for the development of technology-independent instructional media suitable for elementary education contexts in Indonesia.